Comparative studies of magnetic and magnetocaloric properties in amorphous Gd0.67Y0.33 and Gd0.67Zr0.33 films. (January 2017) - Alouhmy, G.; Moubah, R.; Sayouty, E.H.; Lassri, H.
Abstract: Amorphous Gd0.67 ×0.3 (X=Y, Zr) films were grown by RF sputtering and their magnetic and magnetocaloric properties were studied. The magnetic properties were found to be improved in case of Gd0.67 Y0.33 with respect to Gd0.67 Zr0.33, in which the Curie temperature, magnetization and spin wave stiffness were higher for Gd0.67 Y0.33, which we attribute to its larger Gd-Gd distance. The temperature dependence of magnetic entropy change (−ΔSM ) was calculated from the isothermal magnetization. Under a magnetic field change of 3 T, (−ΔSM ) were found to be 2.14 and 1.12 J/kg K, with corresponding relative cooling power (RCP) of 198.86 and 113.2 J/kg, for Gd0.67 Y0.33 and Gd0.67 Zr0.33, respectively. The larger magnetocaloric properties for Gd0.67 Y0.33 are attributed to its higher magnetization. Highlights: The magnetic and magnetocaloric properties of amorphous Gd0.67 Y0.33 and Gd0.67 Zr0.33 films were compared. The Curie temperature, the magnetization and spin wave stiffness are larger for Gd0.67 Y0.33 . The Gd0.67 Y0.33 alloys present better magnetocaloric performance than Gd0.67 Zr0.33 .